2015
DOI: 10.1123/mc.2013-0098
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of Movement Outcome in Space-Time

Abstract: Information entropy of the joint spatial and temporal (space-time) probability of discrete movement outcome was investigated in two experiments as a function of different movement strategies (space-time, space, and time instructional emphases), task goals (point-aiming and target-aiming) and movement speed-accuracy constraints. The variance of the movement spatial and temporal errors was reduced by instructional emphasis on the respective spatial or temporal dimension, but increased on the other dimension. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…It seems that the movement amplitude contributed more influence to movement outcome in the temporal dimension than to movement outcome in the spatial dimension. This finding suggests that movement temporal error is more easily influenced compared to the movement spatial error by the different space-time constraints and movement amplitudes (Hsieh et al, 2013;Lai et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It seems that the movement amplitude contributed more influence to movement outcome in the temporal dimension than to movement outcome in the spatial dimension. This finding suggests that movement temporal error is more easily influenced compared to the movement spatial error by the different space-time constraints and movement amplitudes (Hsieh et al, 2013;Lai et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…It is anticipated that the movement variability in terms of a probabilistic two dimensional space-time approach would be different from the variability measured in the traditional single dimension distribution analysis of spatial or temporal error because it captures a unified index of the collective spatial and temporal uncertainty. Lai et al (2015) showed that joint space-time entropy was sensitive to different speed-accuracy manipulations but did not investigate the speed-accuracy function for joint space-time entropy.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hsieh et al (2015) investigated a unified joint probabilistic entropy estimate of spatial and temporal movement error (Lai et al, 2015;Scott, 1992;Williams, 1997). The results showed a U-shaped joint entropy function under the movement space-time conditions (different spatial and temporal criteria) for all three movement amplitudes.…”
mentioning
confidence: 99%
“…Information entropy is a candidate measure within the concept of information theory models of human information processing (Shannon & Weaver, 1949;Williams, 1997) and it is based on probabilities as a foundation to unify both force and time error of the movement speed and accuracy relation (Hsieh, Pacheco, & Newell, 2015;Lai, Hsieh, & Newell, 2015). An advantage of an information entropy measure is that it is based on the probability of the actual frequency distribution irrespective of the measured movement and force error dimensions and assumptions about a normal distribution.…”
mentioning
confidence: 99%